Gum Chewing for Stimulating Early Recovery of Bowel Function after Postoperative Benign Gynecologic Surgery: A Randomized Controlled Trial - Ekapob Nanthawong; Ussanee Sangkomkamhang; Thananit Sangkomkamhang (The Royal Thai College of Obstetricians and Gynaecologists, 2016)
Objectives:To compare gum chewing and routine postoperative care on recovery of bowel function after laparotomy for benign gynecologic surgery.Materials and Methods:Patients who underwent laparotomy for benign gynecologic diseases at Khon Kaen Hospital from May to August, 2015 were randomly allocated into 2 groups: gum chewing (n= 56) and control group (n= 56). Patients chewed sugarless gum for 15 minutes after 6 hours postoperatively then every 4 hours until the first passage of flatus and the control group had the routine postoperative care.Results: Chewing gum was a statistically significant in reducing time to first flatus compare with routine postoperative care (20.3 ± 8.4 vs 27.3 ± 7.9 hrs, mean difference 6.9 hrs; p < 0.001). Time to tolerate regular diet was also significantly shorter in chewing gum group (47.5 ± 10.8 vs 49.4 ± 6.9 hr, mean difference 1.9 hr; p = 0.04). Postoperative vomiting was significantly less in chewing gum group (13 (23.6%) vs 26; p = 0.002). There were no significant differences between the groups in time to tolerate liquid diet, postoperative nausea, antiemetic drug requirement and length of a hospital stay.Conclusion: Gum chewing associated with early recovery of bowel function in patients undergo laparotomy for benign gynecologic surgery.